Metabolic syndrome and neurological disorders - Farooqui, Tahira; Farooqui, Akhlaq A. (Ames, Iowa : Wiley-Blackwell, 2013)
Metabolic Syndrome and Neurological Disorders brings together information on the cluster of common pathologies which cause metabolic syndrome - abdominal obesity linked to an excess of visceral fat, insulin resistance, dyslipidemia and hypertension - to provide a comprehensive and cutting edge exploration of the link between metabolic syndrome and neurological disorders. Metabolic syndrome is recognized to play a role in neurological disorders such as stroke, Alzheimer's disease, and depression. For the first time in book form, Metabolic Syndrome and Neurological Disorders covers the molecular mechanisms thought to underlie this mirror relationship, as well as how lifestyle and other factors such as oxidative stress and inflammation may play a role in the disease. Grounded in a series of epidemiological studies of metabolic-cognitive syndrome, this book will be a valuable reference for researchers, dietitians, nutritionists, and physicians'--Provided by publisher
Machine generated contents note: Insulin resistance and metabolic failure underlie Alzheimer's disease / Suzanne M. de la Monte & Ming Tong -- Insulin receptor and the pathophysiology of Alzheimer's disease / Johanna Zemva & Markus Schubert -- Contribution of insulin resistance in pathogenesis of Alzheimer's disease / Adnan Erol -- Insulin-leptin signaling in the brain / Vicente Barrios, Emma Burgos-Ramos & Jesus Argente -- The janus face of insulin in brain / Duarte A.I., Candeias E., Correia S.C., Santos R.X., Carvalho C., Cardoso S., Placido A.I., Santos M.S., Oliveira C.R., Moreira P.I. -- Modulation of cognition by insulin and aging: implications for Alzheimer disease / Maite Solas & Maria J. Ramirez -- Contribution of phospholipid, sphingolipids, and cholesterol-derived lipid mediators in the pathogenesis of metabolic syndrome and neurological disorders / Akhlaq A. Farooqui & Tahira Farooqui -- Lipids, cholesterol and oxidized cholesterol in Alzheimer's Amyloid Beta-mediated neurotoxicity / Mun'delanji Vestergaard, Masamune Morita, Tsutomu Hamada & Masahiro Takagi -- Of sound mind and body : dietary lifestyles, promotion of healthy brain aging and prevention of dementia in healthy individuals / Giulio Maria Pasinetti, Amanda Bilski, Lap Ho, Jun Wang, Mario Ferruzzi, Masahito Yamada, Kenjiro Ono & Salvatore Mannino -- Metabolic syndrome as an independent risk factor of silent brain infarction / Jae-Sung Lim & Hyung-Min Kwon -- Neurochemical linkage among metabolic syndrome, Alzheimer's disease, and depression / Undurti N. Das -- Alterations in the endocannabinoid system as a link between unbalanced energy homeostasis, neuroinflammation and neurological and neuropsychiatric disorders / Tiziana Bisogno & Vincenzo Di Marzo -- Metabolic syndrome, Alzheimer's disease, schizophrenia and depression : role for leptin, melatonin, kynurenine pathways and neuropeptides / George Anderson & Michael Maes -- Binge eating and metabolic syndrome / Gnacio Jauregui-Lobera -- Phytochemical principles in the traditional Indian system of medicine used for the management of metabolic syndrome / Syed Ibrahim Rizvi & Neetu Mishra -- Oxidative stress and obesity : their impact on metabolic syndrome / Morihiro Matsuda & Iichiro Shimomura -- Relationship between obesity, inflammation, and insulin resistance / Jean-Philippe Bastard & Bruno Feve -- Involvement of adipocytokines in pathogenesis of insulin resistance, obesity and metabolic syndrome / Hardik Gandhi & Ramachandran Balaraman -- Obesity, inflammation and vascular disease : novel insight in the role of adipose tissue / Calabro P., Golia E., Maddaloni V., Limongelli G., Ziello B., Fimiani F., Romano I.J., Crisci M., Russo M.G., Yeh E.T.H. & Calabro R. -- Is diabetes as a risk factor for Parkinsons diseases? / Akhlaq Farooqui & Tahira Farooqui -- Role of iron in the pathogenesis of diabetes and metabolic syndrome / Lu Cai -- Contributions of AMP kinase to the pathogenesis of type 2 diabetes and neurodegenerative diseases / Mohamed Kodiha, Hicham Mahboubi & Ursula Stochaj -- A[beta] deposition, insulin signaling and tau phosphorylation in animal models of Alzheimer disease and diabetes / Naoyuki Sato & Ryuichi Morishita -- In vivo evidence of the convergence of type-2 diabetes and Alzheimer's disease / Sun Ah Park -- Metabolic syndrome and its impact on cardiovascular disease / John Larry -- Contribution of inflammation, adiponectin, and obesity in cardiovascular diseases / Harald Mangge & Gunter Almer -- Brain and cardiovascular diseases : molecular aspects / Ewa Szczepanska-Sadowska -- Molecular aspects of dietary-exercise regimen for the prevention of metabolic syndrome / Wataru Aoi -- Ghrelin, lipid metabolism and metabolic syndrome / Pablo B. Martinez de Morentin, Sulay Tovar, Ruben Nogueiras, Miguel Lopez & Carlos Dieguez -- Leptin and cognitive function / Jenni Harvey -- Fructose, sugar consumption, and metabolic diseases / Virgile Lecoultre & Luc Tappy -- Inflammation-mediated cognitive and emotional alterations in experimental models of metabolic syndrome / Nathalie Castanon & Sophie Laye -- Future perspectives / Tahira Farooqui & Akhlaq A. Farooqui
Includes bibliographical references and index.
Keywords: Metabolic Syndrome X -- etiology; Metabolic syndrome -- metabolism; Vervous System Diseases -- etiology